Analisis Pengaruh Dana Alokasi Khusus (DAK) Terhadap Pertumbuhan Ekonomi Kabupaten/Kota Penghasil Batubara Provinsi Kalimantan Tengah Tahun 2010-2019 - Melani, Siti Indah; Sopiana, Yunita (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2023)
This study aims to analyze the effect of the Special Allocation Fund (DAK) on the Economic Growth of Coal-Producing Districts/Cities in Central Kalimantan Province in 2010-2019. The data used is secondary data obtained from JDIH of the Ministry of Finance, DJPK of the Ministry of Finance, and the Central Kalimantan Statistics Agency during 2010-2019. The unit of analysis is nine districts/cities in Central Kalimantan Province. This study uses a panel data regression model with the Common Effect Model. The results of this study indicate that DAK is harmful and has no significant effect on the economic growth of coal-producing districts/cities in Central Kalimantan Province.